2020
DOI: 10.14502/tekstilec2020.63.4-13
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of Antibacterial and UV-protective Cotton Fabric by an in situ Synthesis of Silver Particles in the Presence of a Sol-gel Matrix and Sumac Leaf Extract

Abstract: This research presents a new procedure for the chemical modifi cation of cotton fabric, which included a ''green'' in situ synthesis of silver particles using an extract of sumac leaves as a reducing agent. To increase the adsorption ability of silver cations, a sol-gel matrix was previously created on cotton fabric using an organic-inorganic precursor sol-gel. The presence of silver particles on the cotton fabric was confi rmed by scanning electron microscopy and energy-dispersive X-ray spectroscopy. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The transmittance spectrum of the individual coated sample was recorded over the UV–vis spectral range of 200–700 nm wavelengths (200–280 nm is UV-C, 280–315 nm is UV-B, 315–400 nm is UV-A, and 400–700 nm is the Vis region) by means of a Lambda 900 UV–vis-NIR spectrophotometer (Perkin Elmer, Waltham, MA, USA) with an integrated sphere, at a scanning speed of 450 nm per min and a resolution of 5 nm. In addition, the UV-shielding capability was expressed as Ultraviolet Protective Factor (UPF), which was calculated according to the following Equation (3) [ 18 ]: where E λ is a CIE relative erythemal spectral effectiveness; S λ is a solar spectral irradiance; T λ is a spectral transmittance of the fabric; Δ λ is a wavelength step in nm; and λ is a wavelength in nm.…”
Section: Methodsmentioning
confidence: 99%
“…The transmittance spectrum of the individual coated sample was recorded over the UV–vis spectral range of 200–700 nm wavelengths (200–280 nm is UV-C, 280–315 nm is UV-B, 315–400 nm is UV-A, and 400–700 nm is the Vis region) by means of a Lambda 900 UV–vis-NIR spectrophotometer (Perkin Elmer, Waltham, MA, USA) with an integrated sphere, at a scanning speed of 450 nm per min and a resolution of 5 nm. In addition, the UV-shielding capability was expressed as Ultraviolet Protective Factor (UPF), which was calculated according to the following Equation (3) [ 18 ]: where E λ is a CIE relative erythemal spectral effectiveness; S λ is a solar spectral irradiance; T λ is a spectral transmittance of the fabric; Δ λ is a wavelength step in nm; and λ is a wavelength in nm.…”
Section: Methodsmentioning
confidence: 99%
“…All samples show particularly high antibacterial activity against S. aureus (R = 99.9%). Filipič et al also reported that maximum S. aureus reduction (100%) could be achieved on cotton fabric with a sol-gel matrix and in situ synthesized Ag particles using sumac leaf extract [25]. Equivalent antimicrobial activity was obtained with cotton fabrics impregnated with Ag NPs in situ synthesized using green tea leaves, avocado seed, goldenrod flowers, and pomegranate peel extracts [40].…”
Section: Antimicrobial Activity Of Textile Nanocompositesmentioning
confidence: 98%
“…Small amounts of NPs can impart extraordinary antimicrobial activity to textile fibers using relatively simple processing routes. Keeping in mind that cotton is widely used in the fabrication of medical textiles and that the need for antimicrobial textiles is continually growing, cotton fabric is commonly used as a substrate for impregnation with biosynthesized Ag-based NPs [20][21][22][23][24][25]. In this work, a simple synthesis route without purification of plant extracts and without using any additional stabilizing agents is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it has been used in the processing and finishing of textiles to impart functional benefits [ 15 ]. Polymeric nanostructures, metal oxides, carbon nanotubes, clay nanoparticles (NPs), carbon black, graphite nanofibers, and other nanomaterials provide unprecedented textile performance, such as being hydrophilic and hydrophobic, antistatic, wrinkle-resistant, antimicrobial, antiodor, self-cleaning, and antiUV [ 16 , 17 , 18 , 19 , 20 , 21 ]. Inorganic NPs, especially TiO 2 , ZnO, SiO 2 , Cu 2 O, CuO, Al 2 O 3 , and reduced graphene oxide NPs, are more commonly used than organic NPs due to their thermal and chemical durability at high temperatures, permanent stability under UV rays, and non-toxicity [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%